Effect of Authentic Leadership Educational Program for Head Nurses on Staff Nurses' Organizational Commitment - Aziza Z. F. Ali; Ehsan S. S. Saad; Fadhah T. Alshammari (Evidence-Based Nursing Research)
Context: Authentic leadership is required to build trust and achieving positive organizational outcomes. Organizational commitment acts as one of the outcomes of authentic leadership. Head nurses, as leaders can use an authentic leadership style that positively influence staff nurses and increase their organizational commitment.